Surface treatments of zirconia to enhance bonding durability - Melo, R. M. [UNESP]; Souza, R. O.A.; Dursun, E.; Monteiro, E. B.C.; Valandro, L. F.; Bottino, M. A. [UNESP] (Operative Dentistry, 2015)
This article reviewed the surface treatments used most often to improve adhesion between zirconia and adhesive cements, focusing on their capacity to provide long-term bonding. Traditional and new treatments for zirconia bonding were searched. Some new treatments were discussed along with topographical views of the modified zirconia. New methods, such as selective infiltration etching and the low-fusing glassy porcelain application are promising, but more research is needed.